"And Serve the Cause of Freedom": American Food Conservation in the First World War. Issue 1 (2nd January 2017) - Nordstrom, Justin
Abstract: This article argues that the United States Food Administration (USFA) employed contradictory imagery and rhetoric to motivate Americans to conserve wheat, beef, sugar, pork, and other essential foods during the First World War. While USFA posters emphasized patriotism, solidarity, and euphoric national loyalty, they simultaneously employed dystopian portrayals of hunger, chaos, and madness. Yet neither uplifting nationalism nor overt fearmongering significantly altered the food choices of many Americans. While USFA efforts did adjust food consumption in some categories, in the aggregate, Americans ate more restricted foods during the war as compared to prewar levels. America played a role in alleviating food shortages in the 1910s as a result of increased farm production, not decreased consumption.